(untitled) (REMUNOM, 2024)
Studies on Autism Spectrum Disorder (ASD) have been conducted for more than 60 years, but many questions persist. The increase in the prevalence of ASD and its complexity demand an in-depth analysis. The possible association between maternal vitamin D deficiency and increased risk of ASD stands out as an intriguing and public health-relevant field of research. Vitamin D supplementation during pregnancy can be a preventive and therapeutic strategy for ASD, but more studies are still needed to confirm this hypothesis and determine the ideal dose and period of intervention. This article aims to analyze, through bibliographical research, whether there is evidence that vitamin D deficiency during pregnancy contributes to the development of ASD. Regarding methodology, this is a review of the literature covering epidemiological aspects of ASD, signs and symptoms, vitamin D metabolism, the role of vitamin D in embryogenesis and the relationship between vitamin D deficiency and the development of ASD. It should be noted that vitamin D deficiency during pregnancy emerges as a relevant environmental factor in the development of ASD. The review highlights the importance of vitamin D in embryogenesis and its possible relationship with ASD. Maintaining adequate levels of vitamin D during pregnancy is crucial for optimal brain development and can positively impact the prevention of ASD. Therefore, this study sought to contribute to the understanding of the complex interactions between vitamin D and ASD, promoting scientific and clinical discussions with potential impact on public health.